Emerging evidence on the pathobiology of mucositis - Al-Dasooqi, Noor; Sonis, Stephen T.; Bowen, Joanne M.; Bateman, Emma; Blijlevens, Nicole; Gibson, Rachel J.; Logan, Richard M.; Nair, Raj G.; Stringer, Andrea M.; Yazbeck, Roger; Elad, Sharon; Lalla, Rajesh V. (Supportive care in cancer, 2013)
Background Considerable progress has been made in our understanding of the biological basis for cancer therapy-induced mucosal barrier injury (mucositis). The last formal review of the subject by MASCC/ISOO was published in 2007; consequently, an update is timely. Methods Panel members reviewed the biomedical literature on mucositis pathobiology published between January 2005 and December 2011. Results Recent research has provided data on the contribution of tissue structure changes, inflammation and microbiome changes to the development of mucositis. Additional research has focused on targeted therapy-induced toxicity, toxicity clustering and the investigation of genetic polymorphisms in toxicity prediction. This review paper summarizes the recent evidence on these aspects of mucositis pathobiology. Conclusion The ultimate goal of mucositis researchers is to identify the most appropriate targets for therapeutic interventions and to be able to predict toxicity risk and personalize interventions to genetically suitable patients. Continuing research efforts are needed to further our understanding of mucositis pathobiology and the pharmacogenomics of toxicity.